Ta’wil Al-Qur’an Imam Al-Ghazali: Telaah Metodologis atas Kitab Tafsir al-Imam al-Ghazali Karya Muhammad al-Rihani - Basid, Abd.; Naufal Maulana, Ach.; Robith Lutfillah, Wahid (FIRDAUS, 2023)
The figure of the author of the book Ihya' 'Ulum al-Din, Imam Al-Ghazali, in the field of interpretation is not yet widely known by the public, even though he has made quite a large contribution to the discourse on the study of interpretation of the Qur'an, with his intelligent and "liberal" ideas. ” in understanding and interpreting the Koran. He once wrote a work of interpretation, Yaqut al-Ta'wil fi Tafsir al-Tanzil, which reached 40 volumes, although we cannot inherit this precious work. In addition, he also wrote a book on the study of the Qur'an, Jawahir al-Qur'an and Qanun al-Ta'wil and a particular chapter, Fahm al-Qur'an wa Tafsiruh bi al-Ra'yi min Ghairi al-Naql as stated in the book Ihya' 'Ulumu al-Din. For this reason, this research is planned to confirm al-Ghazali's capacity as a mufassir, by examining one of the books that collects his interpretations of the Qur'an as presented in the book Tafsir al-Imam al-Ghazali compiled by Muhammad al-Rihani . This research will use a qualitative-descriptive research paradigm, which seeks to describe the ways and methods of Imam Al-Ghazali's interpretation of Al-Qur'an verses from the book Tafsir al-Imam al-Ghazali and books, books and journal articles related to the research theme. This. From the several data sources above, all data that meets the needs of the theme is taken and analyzed using content analysis. Some of the discussions planned and considered important in this research are; 1) Imam Al-Ghazali's intellectual biography, 2) Tafsir al-Imam al-Ghazali, Al-Ghazali in the Tafsir Al-Qur'an Discourse, and 3) Imam Al-Ghazali's concept of Ta'wil in the book Tafsir al-Imam al- Ghazali